A head-to-head comparison of conjugation methods for VHHs: Random maleimide-thiol coupling versus controlled click chemistry - Marc V.A. van Moorsel; Rolf T. Urbanus; S. Verhoef; C.A. Koekman; Maurice Vink; T. Vermonden; Coen Maas; Gerard Pasterkamp; Raymond M. Schiffelers (Elsevier, 2019)
Targeted delivery of therapeutics is an attractive strategy for vascular diseases. Recently, variable domains of heavy-chain-only antibodies (VHHs) have gained momentum as targeting ligands to achieve this. Targeting ligands need adequate conjugation to the preferred delivery platform. When choosing a conjugation method, two features are critical: a fixed and specified stoichiometry and an orientation of the conjugated targeting ligand that preserves its functional binding capacity. We here describe a comparison of popular maleimide-thiol conjugation with state-of-the-art "click chemistry" for conjugating VHHs. First, we demonstrate the modification of VHHs with azide via Sortase A mediated transpeptidation. Subsequently, optimal clicking conditions were found at a temperature of 50 °C, using a 3:1 M ratio of DBCO-PEG:VHH-azide and an incubation time of 18 h. Second, we show that stoichiometry was controllable with click chemistry and produced defined conjugates, whereas maleimide-thiol conjugation resulted in diverse reaction products. In addition, we show that all VHHs - independent of the conjugation method or conjugated residue - still specifically bind their cognate antigen. Yet, VHH's functional binding capacities after click chemistry were at least equal or better than maleimide thiol conjugates. Together these data underline that click chemistry is superior to maleimide-thiol conjugation for conjugating targeting ligands. Keywords: Targeted delivery, Variable domains of heavy chain only antibodies (VHHs), Site specific conjugation, Maleimide-thiol conjugation, Copper free strain-promoted azide alkyne cycloaddition (SPAAC), Click chemistry